"Let Me Double‐Check That": A Challenge for Conciliationism. Issue 3 (21st December 2021) - Anaya, Alfonso
Abstract: Double‐checking one's reasoning is a perfectly normal way of responding to a disagreement between peers. I argue that conciliationist approaches lack the resources to accommodate this phenomenon adequately. On the one hand, conciliationists cannot claim that double‐checking is a rationally impermissible response to disagreement because a compelling case for its permissibility appeals to arguments analogous to those often used by conciliationist in favour of their own view. On the other, they lack the resources to accommodate double‐checking as a rationally permissible response to disagreement. To show this, I draw a distinction between strong and moderate versions of conciliationism . The strong version accepts, whereas the moderate version rejects, that the conciliatory obligation exhausts the rational requirements engendered by disagreements. Strong conciliationists cannot explain the motivation for someone to double‐check if they have followed the conciliationists advice. Moderate conciliationists who try to make space for double‐checking are forced to concede that disputants can respond rationally to disagreement without lowering their confidence in the disputed belief.